Emission of volatile organic compounds during combustion process in a miniature turbojet engine - Janicka, Anna Barbara; Zawiślak, Maciej; Gawron, Bartosz; Górniak, Aleksander; Białecki, Tomasz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Aviation is one of the fastest growing modes of transport. Due to the growing number of flights, the consumption of aviation fuels (mainly jet fuels) keeps increasing. The combustion process in the aircraft engine results in harmful exhaust emissions having an adverse impact on the environment. Alternative fuels based on bio-components and biofuels are a way of reducing the harmful exhaust emissions. Analyses and measurements performed on real aircraft engines are complex and expensive. For this reason, increasingly more research and development projects have been carried out on small- -scale engines. This paper presents investigations into volatile organic compound emissions from jet fuel combustion in a miniature turbojet engine. Based on chromatography tests, the compositions of exhaust gases produced by the jet engine fed with various fuels were determined, which in turn led to evaluation of its toxicity and harmfulness. Conventional fossil-based fuel Jet A-1 and a blend of Jet A-1 with 25 vol. % of biobutanol were tested at the same fuel flow rates. The engine working parameters such as, e.g., thrust or emission index have been determined with respect to the type of fuel. The test resultshave been compared and analyzed.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 57-67
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma